Risk factors for renal impairment in primary aldosteronism: a retrospective study - Qin, Shuitao; Li, Jianling; Wu, Siying; Li, Sen; Huang, Jing; Yu, Jie; Wei, Chaoping; Wei, Lixia; Zhu, Shuangbei; Chen, Shanshan; Chen, Meilan (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate the risk factors associated with renal impairment among patients diagnosed with primary aldosteronism (PA).MethodsThis study enrolled 147 PA patients who were initially classified into hypokalemic (n=56) and normokalemic (n=91) groups according to serum potassium levels, followed by subgroup stratification using combined adrenal venous sampling (AVS) and computed tomography (CT) diagnostic data. For comparison, 280 patients diagnosed with essential hypertension (EH) served as the control group. Data on general patient characteristics and biochemical markers from blood and urine samples were collected. The analysis involved comparing these indicators across groups and performing binary logistic regression to identify potential risk factors for renal damage.ResultsWhen compared to the EH group, the PA group had lower serum potassium and heart rate (P < 0.05), but higher diabetes prevalence, standing plasma aldosterone concentration (PAC), serum sodium, albumin-to-creatinine ratio (ACR), and 24-hour urinary potassium excretion (P < 0.05). Among PA patients, the hypokalemic subgroup showed higher systolic/diastolic blood pressures, PAC, serum sodium, 24-hour urinary potassium, microalbumin, and ACR versus the normokalemic subgroup (P < 0.05). Compared with the IHA subgroup, the APA subgroup showed significantly higher standing PAC levels (P < 0.05). The classic APA subgroup exhibited elevated 24-hour urinary microprotein, ACR values, and hypokalemia prevalence relative to non-classic unilateral cases (P < 0.05). However, no significant differences emerged between unilateral and bilateral aldosterone secretion groups for serum potassium, PAC levels, or renal damage markers (P>0.05). Hypokalemia (OR=3.027) and urinary potassium (OR=1.052) predicted proteinuria (P<0.05).ConclusionThis study demonstrates that renal impairment is more pronounced in PA patients than in those with EH. Notably, the classic APA subtype exhibits particularly severe damage, specifically manifested by elevated urinary microalbumin excretion. Furthermore, concomitant hypokalemia in PA patients is associated with more severe renal impairment. Hypokalemia and increased 24-hour urinary potassium excretion emerge as key risk factors for renal damage within this patient population.